Analisis resiko kebencanaan gempa bumi data mikrotremor di Desa Fulolo Kecamatan Alasa Kabupaten Nias Utara - Asronj Bakkit Simanjuntak; Gatot Yuliyanto; Udi Harmoko (Youngster Physics Journal, 2017)
The Measurement of the microtremor has been conducted in the Village of Fulolo, Alasa Subdistrict, North Nias District. The aim of this study is to determine the parameters of HVSR in the form of the dominant frequency value (f0) and amplification factor (A0) and the parameters of soft sediment thickness (H), seismik vulnerability index (Kg), peak ground acceleration/PGA (α) and ground shear strain (γ) as well as analyzing the earth quake disaster risk  in the Village of Fulolo, Alasa District, North Nias District. Microtremor measurements done on 5 points measurement and microtremor’s data were analyzed using Horizontal to Vertical Spectral Ratio’s method. The HVSR analysis is in the dominant frequency (f0) value and amplification (A0) value. Then calculate the thickness of soft sedimentary , the value of peak ground acceleration/PGA(α), the value of seismic vulnerability index (Kg) and the value of ground shear strain (γ).The results showed that the village of Fulolo have dominant frequency (f0)  distribution grade range up 0,954 Hz to 7,149 Hz, the value of amplification (A0) ranges up 0,546 to 7,505, the value of the thickness of soft sedimentary (H) ranges up 8,945 meters t 112,21 meters, the value of peak ground acceleration (α) ranges up 71,78 gal to 194,11 gal, the seismic vulnerability index (Kg) ranges up 2,06 x 10-07 (1/cm s2) to 1,86 x 10-05 (1/cm s2) and the value of ground shear strain (γ) range up 1,031 x 10-04 to 1,338 x 10-03. Area that are high risk of experiencing the ravages of earthquakes are Fulolo 3rd, Fulolo 4th, Fulolo 5th on the Gunung Sitoli Formations (QTg) because of those have a thick layer of soft sediments so that third of the area have a dominant low frequency (f0) and resulting low amplification factor (A0) are high as well as at risk for experiencing shifting rock and deformation of surface layer due to the propagation of earthquake waves.Keywords: Microtremor, HVSR, Dominant Frequency, Amplification, Peak Ground Acceleration, Seismic Vulnerability Index and Ground Shear Strain